Implementasi Blended Learning sebagai Alternatif Pembelajaran PAI dalam Materi Salat Jenazah - Yayang Purnama Sari; Asep Dudi Suhardini (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. On this basis, this research is focused on the learning process and the factors that support and hinder the implementation of Blended Learning so that teaching and learning activities can be carried out during the covid-19 pandemic at SMA X class XI Especially in the PAI learning material for the funeral prayer. The approach used is a qualitative descriptive approach with a case study method. The research objects selected in this study were 29 students of SMA X class XI and the interviewees were 3 students and 3 students. The data collection techniques used were interviews, observation, and documentation studies. The results of this study are (1) Knowing how teachers plan Islamic religious education lessons by using the implementation of blended learning as an alternative to PAI learning in the material for praying the corpses of class XI at X High School. (2) Knowing How Teachers implement Islamic Religious Education Learning by using the Implementation of Blended Learning as an Alternative for PAI Learning in the Material of the XI Class XI Corpse Prayer at X High School. (3) Knowing How Teachers Carry Out Evaluation of Islamic Religious Education Learning by using the Implementation of Blended Learning as an Alternative for Islamic Religious Education in Class XI Body Prayer Materials at X High School (4) Knowing What are the obstacles in the Implementation of Islamic Religious Education Learning by using the Implementation of Blended Learning as an Alternative PAI Learning in Materials for Class XI Corpse Prayers. Abstrak.Penelitian ini difokuskan pada proses pembelajaran dan faktor yang mendukung dan menghambat penerapan pembelajaran Blended Learning agar dapat terlaksananya kegiatan belajar mengajar dimasa pandemi covid-19 di SMA X kelas XI Terkhusus pada pembelajaran PAI materi salat jenazah. Pendekatan yang di gunakan adalah pendekatan deskriptif kualitatif dengan metodae studi kasus. Objek penelitian yang di pilih dalam penelitian ini siswa siswi SMA X kelas XI yang berjumlah 29 orang dan yang wawancari yaitu 3 orang siwa dan 3 orang siswi. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan studi dokumentasi. Hasil dari penelitian ini (1) Mengetahui Bagaimana Guru dalam merencanakan Pembelajaran Pendidikan Agama Islam dengan menggunakan Implementasi Blended Learning sebagai Alternatif Pembelajaran PAI dalam Materi Salat Jenazah Kelas XI di SMA X. (2) Mengetahui Bagaimana Guru dalam melaksanaan Pembelajaran Pendidikan Agama Islam dengan menggunakan Implementasi Blended Learning sebagai Alternatif Pembelajaran PAI dalam Materi Salat Jenazah Kelas XI di SMA X. (3) Mengetahui Bagaimana Guru Melaksanakan Evaluasi Pembelajaran Pendidikan Agama Islam dengan menggunakan Implementasi Blended Learning sebagai Alternatif Pembelajaran PAI dalam Materi Salat Jenazah Kelas XI di SMA X (4) Mengetahui Apa kendala dalam Pelaksanaan Pembelajaran Pendidikan Agama Islam dengan menggunakan Implementasi Blended Learning sebagai Alternatif Pembelajaran PAI dalam Materi Salat.